NS2 – Based Experimental Analysis of Throughput for TCP and UDP Traffic During Link Failure of The Network - Gupta, Anshul; Mamgain, Kanishk; Singh, Maninder; Chhabra, Amit (Iraqi Journal of Science, 2024)
Link failure refers to the failure between two connections/nodes in a perfectly working simulation scenario at a particular instance. Transport layer routing protocols form an important basis of setting up a simulation, with Transmission Control Protocol and User Datagram Protocol being the primary of them. The research makes use of Network Simulator v2.35 to conduct different simulation experiments for link failure and provide validation results. In this paper, both protocols, TCP and UDP are compared based on the throughput of packets delivered from one node to the other constrained to the condition that for a certain interval of time the link fails and the simulation time remains the same for either of the protocols. Overall, this analysis is based on determining the performance of both protocols with a fixed packet size and bandwidth. This analysis, performed with the help of NS2 and XGraph, shows that the transport layer protocol, UDP acts better than TCP in terms of throughput. This opens the questions to other fellow researchers of how different metrics act in both the cases when a link failure occurs. In UDP, the throughput drops less as compared to the TCP at the time of the link failure regardless of if simulation was executed for different time periods i.e., 70,100,300,900 and 1000 seconds. The link failure interval is also varied from 10,15,20,40,350 and 440 seconds to generalize and validate the performance of the network during the interval.